Rapid Change in the Orbital Period of the Remnant of Nova Scorpii AD 1437 (IGR J17014-4306) - Lei Zang; Shengbang Qian; Li Zhang; Qibin Sun; Linfeng Chang; Berto Monard; Gordon Myers; Franz-Josef Hambsch (The Astrophysical Journal)
IGR J17014-4306 is the longest orbital period (12.8 hr) deep-eclipsing intermediate polar known, where a massive white dwarf (WD) accretes matter from its companion star via an accretion disk. Based on photometric observations from the Transiting Exoplanet Survey Satellite space telescope and the American Association of Variable Star Observers database, 70 eclipse timings were determined. It was also confirmed that the spin pulse profile of the WD does change, which is due to the amplitude variation with opposite trends in spin frequency and its first harmonic. This may be related to fluctuations in the accretion rate. The spin period shows slight fluctuations but no significant changing trends. We constructed the O – C diagram and discovered that the orbital period is increasing at a high rate of ${\dot{P}}_{orb}=+4.3(3)× 1{0}^{-7}days· {yr}^{-1}=+0.037(3){\rm{s}}· {yr}^{-1}$ , which is comparable to those detected in compact binary supersoft X-ray sources and recurrent novae. This continuous increase in the orbital period is caused by the mass transfer from the less-massive companion to the WD on its thermal timescale at a high rate. All these findings suggest that IGR J17014-4306 is an interesting target to investigate nova eruption, the real angular momentum loss mechanism, and the overall evolution of cataclysmic variables.